Relationship Clean-Up Time: Using Meta-Analysis and Path Analysis to Clarify Relationships Among Job Satisfaction, Perceived Fairness, and Citizenship Behaviors † - Fassina, Neil E.; Jones, David A.; Uggerslev, Krista L. (Journal of Management, 2008)
Although perceived fairness and job satisfaction predict organizational citizenship behaviors (OCB), researchers have pondered the conceptual relationships among these constructs. Using path analysis on meta-analytically derived coefficients, the authors compared four models: full mediation (job satisfaction mediates fairness-OCB relationships), partial mediation, independent effects, and a spurious effects model (the job satisfaction—OCB relationship is spurious because perceived fairness is a common cause). The authors found greatest support for the independent effects model: Job satisfaction and different types of perceived fairness accounted for unique variance in OCB dimensions. The article discusses implications for research and practice, and offers suggestions to advance theory in this area.